Climate warming reduces soil gaseous nitrogen losses in a temperate forest - Kai Huang; Di Wu; Dongwei Liu; Yihang Duan; Peter Dörsch; Klaus Butterbach-Bahl; Xiaoming Fang; Yuqi Liu; Chao Wang; Haoming Yu; Lingrui Qu; Jingwen Xu; et al. (Proceedings of the National Academy of Sciences, 2025)
Global warming is projected to accelerate ecosystem nitrogen (N) loss via gaseous pathways, thereby decreasing N availability, a critical nutrient for primary productivity and carbon sequestration. However, the models forecasting this ecosystem N loss are based on laboratory experiments that are inherently uncertain and have had few in situ validations. Over 6 y, we measured ~200,000 soil nitric oxide (NO; an air pollutant) and nitrous oxide (N 2 O; a powerful greenhouse gas) fluxes and used an upscaling approach to estimate N 2 fluxes after warming a temperate forest by 2 °C. Against thermodynamic theoretical predictions, warming unequivocally lowered emissions of NO by 19% and of N 2 O by 16%. These lower gaseous N losses were not explained by complete reduction of NO and N 2 O to N 2 , leaching, nor plant uptake, but rather by the warming-induced drying of soils that constrained microbial activity, consistent with other warming experiments where precipitation was less than 1,000 mm y −1 . Our findings challenge ecosystem model assumptions where warming, alone, accelerates N emissions and underscores how warming-induced losses in soil moisture and shortened freeze-thaw periods can offset temperature effects. Our data underscore the need for explicit consideration of in situ soil moisture when predicting changes on the terrestrial N cycle as the planet warms.